> 数学 >
已知函数f (x )满足f(1)=1/4,4f(x)f(y)=f(x+y)+f(x-y)(x,y属于R),则f(2010)=?
f(x+2)=-f(x-1)
即f(x)=f(x+6)
人气:135 ℃ 时间:2019-08-23 05:59:35
解答
取y=1,则 4f(x)f(1)=f(x+1)+f(x-1)即 f(x)=f(x+1)+f(x-1)所以 f(x+1)=f(x+2)+f(x) (在上式中,以x+1代替x)两式相加,得 f(x+2)+f(x-1)=0所以 f(x+2)=-f(x-1)因此,f(x+6)=f[(x+4)+2]=-f[(x+4)-1]=-f(x+3)=-f[(x+1)+2]=f...本人愚钝,再问一下f(x+6)=f[(x+4)+2]=-f[(x+4)-1]=-f(x+3)=-f[(x+1)+2]=f[(x+1)-1]=f(x)到f(2010)=f(335*6)=f(0)是怎么来的2010 一直减 6 ,减了 335 次后为 0 ,因此 f(2010)=f(2004)=f(1998)=.......=f(0) .
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版